A STUDY ON DOMINATION IN GRAPHS (International Journal of Food and Nutritional Sciences, 2022)
This thesis entitled “SOME CONTRIBUTIONS TO THE THEORY OF DOMINATION IN GRAPHS” is in the field of graph theory in mathematics. Graphs are basic combinatorial structures. Graphs arose as diagrams representing specific relations among a set of objects. In many disciplines we are faced with situations in which we want to find out how or whether a finite number of objects are related. If the relation is symmetric we can model the situation by a graph. So graph theory as wide applications in the field of computer science, operation research and social science etc.